2021
DOI: 10.1097/gox.0000000000003500
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Printed Customized Adjustable Mallet Finger Splint: A Cheap, Effective, and Comfortable Alternative

Abstract: Summary Mallet finger deformity is a common and debilitating injury of the fingertip, accounting for 10% of all tendon and ligament injuries. It involves a disruption of the terminal extensor mechanism of the distal phalanx. Patients can experience significant pain and swelling of the fingertip and have significant morbidity without treatment. Nonoperative treatment using joint immobilization with splints is the mainstay of management. Traditionally, prefabricated and thermoplastic splints have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Except this, no difference was observed in the evaluations performed in shorter and longer periods 18 . In a study, the position of the adjustable splint produced with a 3D printer in mallet finger was examined using x-ray and it was found that it was effective in terms of correction 19 . In our results, we found that the finger splint made of thermoplastic material does not allow any flexion in the PIP joint, but there is very less flexion movement in the DIP joint.…”
Section: Discussionmentioning
confidence: 99%
“…Except this, no difference was observed in the evaluations performed in shorter and longer periods 18 . In a study, the position of the adjustable splint produced with a 3D printer in mallet finger was examined using x-ray and it was found that it was effective in terms of correction 19 . In our results, we found that the finger splint made of thermoplastic material does not allow any flexion in the PIP joint, but there is very less flexion movement in the DIP joint.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of better performance of the customized splints, when compared with prefabricated ones, is found in the literature [11,12]. Both these types of splints can be fabricated using different types of materials available such as plaster, fiberglass, metal, foam, thermoplastics, carbon fiber, and other materials [13,14]. Also, there are different types of fabrication techniques that are used to produce these splints [14].…”
Section: Introductionmentioning
confidence: 99%